Isolation of cellulolytic bacteria from soil sample and production of cellulase and its purification - Khanom, Shabrina (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of M.Sc. in Biotechnology, 2018.